New Banks in Midst of Fintech and Neobanks: English - Adrian Hidayat (eCo-Buss, 2021)
In the year of 2021more and more challenging. The banking industry facing the urgency of the fundamental reinforecement. No one can predict that the affect of COVID-19 pandemic has already 1 year and the waves affected financial and economy in the country. The banking industry are suffering so much, and the intermediary system is quite slow, especially in the credit granting to banking-customer. The business is practically slowing down and even more, they are on the critical situations, therefore the credit-demand is also slowing down. At the same time, credit quality is becoming worse scenario, due to so many creditor facing bad business situation, and therefore they can not pay the credit installment. On this 2021 situation, the banking industry can not wait preparing the future financial-technology (Fintech), such as developing the infrastructure as well as the products to gain more customer and giving more benefits on digital payment system.